Atopic Dermatitis in Children: Current Clinical Guidelines for Diagnosis and Therapy - Leyla S. Namazova-Baranova; Alexander A. Baranov; Anna A. Kubanova; Natalia I. Ilina; Olga M. Kurbacheva; Elena A. Vishneva; Gennadiy A. Novik; Fedor I. Petrovskii; Svetlana G. Makarova; Nikolai N. Murashkin; Anna A. Alekseeva; Liliia R. Selimzianova; et al. ("Paediatrician" Publishers LLC, 2016)
Atopic dermatitis is a chronic multifactorial skin disease that is common enough in childhood. The article presents the current data on epidemiology and dynamics of incidence of pathological symptoms, pathogenesis basics, and key factors of the disease development, shows the current classification of the disease. The authors consider in detail the key principles of the diagnosis and peculiarities of a clinical aspect depending on age. Algorithms of a therapeutic approach, as well as basics of an individual hypoallergenic diet are proposed. General recommendations and possible prognosis for pediatric patients with atopic dermatitis are given.